INTERPERSONAL COMMUNICATION OF PRISON OFFICERS IN SECURITY CONTROL AT CLASS I PENITENTIARY IN MEDAN - Setiawan, Achmad Gilang; Santoso, Iman (Universitas Nusa Cendana, 2025)
This research examines the interpersonal communication of Class I Medan Correctional Institution (Lapas) officers in security control. With the increasing challenges of maintaining security within prisons, it is important for officers to adopt a positive and effective communication approach. The purpose of this study is to identify factors that influence interpersonal communication and its impact on security stability in prisons. The method used is a qualitative approach through interviews with officers and prisoners, as well as field observations to obtain in-depth data. The results show that the lack of training in positive communication, high levels of stress, differences in communication styles, and the limited number of officers are the main obstacles in managing effective communication. In conclusion, to improve security at Medan Class I prisons, better training for officers in interpersonal communication is needed, as well as strategies that can reduce stress and facilitate more positive interactions with prisoners. Keywords: Interpersonal Communication; Correctional Institution; Security